The given sequence is
1, -2, 4, -8, ....,
Multiply the 1st term by -2 to obtain 1*(-2) = -2 (the 2nd term)
Multiply the 2nd term by -2 to obtain -2*(-2) = 4 (the 3rd term)
Multiply the 3rd term by -2 to obtain -2*(4) = -8 (the 4th term)
Answer:
Anet is incorrect.
This is a geometric sequence with a common ratio of -2.
Initial size = 24 (This is the 1st term in the sequence)
2nd term = 24 +5 = 24 + (2-1)*5
3rd term = 24 + 5 + 5 = 24 +(3-1)*5
By induction, the n-th term is
A(n) = 24 + (n-1)*5
Answer:
The given formula is correct.